Front Cover Image, Volume 78, Issue 5. Issue 5 (20th April 2022) - Zhang, Shuyun; Liu, Hang; Yang, Na; Xiong, Lixia; Wang, Baolei
Abstract : The cover image is based on the Research Article Synthesis and evaluation of novel xanthine‐acrylamides and xanthine‐acrylates as insecticidal agents by Shuyun Zhang et al., https://doi.org/10.1002/ps.6834 . Abstract : The cover image is based on the Research Article Synthesis and evaluation of novel xanthine‐acrylamides and xanthine‐acrylates as insecticidal agents by Shuyun Zhang et al., https://doi.org/10.1002/ps.6834 .